NcRNAs: a potential treatment for spinal cord injury - Bao, Jie; Zhi, Wenhui; Qi, Sheng; Mo, Haolong; Liu, Ruzhuan; Guo, Chunhui (Frontiers in Cellular Neuroscience, 2025)
Spinal cord injury (SCI) is a serious disorder that affects sensory, motor, and autonomic functions. Its pathological process is divided into two stages: primary and secondary injury. The secondary injury involves a variety of biological cascade reactions, leading to an imbalance in the spinal cord microenvironment. Non-coding RNAs (ncRNAs) play a crucial regulatory role in the pathophysiological process of spinal cord injury, including long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs), all of which are involved in processes such as axonal regeneration, oxidative stress, inflammatory response, autophagy, and apoptosis. Although the pathophysiological process of spinal cord injury has been partially elucidated, its pathogenesis is not yet fully understood, and effective treatments are limited. This article reviews the regulatory role and molecular mechanisms of ncRNAs in the development and progression of spinal cord injury and proposes strategies for treating spinal cord injury by regulating ncRNAs.